The Tetracycline Resistance Gene, tet(W) in Bifidobacterium animalis subsp. lactis Follows Phylogeny and Differs From tet(W) in Other Species - Nøhr-Meldgaard, Katrine; Struve, Carsten; Ingmer, Hanne; Agersø, Yvonne (Frontiers in Microbiology, 2021)
The tetracycline resistance gene tet(W) encodes a ribosomal protection protein that confers a low level of tetracycline resistance in the probiotic bacterium Bifidobacterium animalis subsp. lactis. With the aim of assessing its phylogenetic origin and potential mobility, we have performed phylogenetic and in silico genome analysis of tet(W) and its flanking genes. tet(W) was found in 41 out of 44 examined B. animalis subsp. lactis strains. In 38 strains, tet(W) was flanked by an IS5-like element and an open reading frame encoding a hypothetical protein, which exhibited a similar GC content (51-53%). These genes were positioned in the same genomic context within the examined genomes. Phylogenetically, the B. animalis subsp. lactis tet(W) cluster in a clade separate from tet(W) of other species and genera. This is not the case for tet(W) encoded by other bifidobacteria and other species where tet(W) is often found in association with transferable elements or in different genomic regions. An IS5-like element identical to the one flanking the B. animalis subsp. lactis tet(W) has been found in a human gut related bacterium, but it was not associated with any tet(W) genes. This suggests that the IS5-like element is not associated with genetic mobility. tet(W) and the IS5 element have previously been shown to be co-transcribed, indicating that co-localization may be associated with tet(W) expression. Here, we present a method where phylogenetic and in silico genome analysis can be used to determine whether antibiotic resistance genes should be considered innate or acquired. We find that B. animalis subsp. lactis encoded tet(W) is part of the ancient resistome and thereby possess a negligible risk of transfer.